Islamic Wealth Management: Empowerment of Inherited Assets in Sharia-Based Productive Economic Development - Hadi, Muhammad; Alwahidin; Tonasa , Muh (Institut Agama Islam Negeri (IAIN) Sultan Amai Gorontalo, 2024)
This study develops an operational framework that integrates Sharia principles, modern management practices, and socioeconomic impact measurement in the context of empowering inheritance assets, using a qualitative approach with an integration of Islamic financial theory analysis methods and empirical studies. The results of the study indicate that the implementation of an Islamic wealth management-based inheritance management model has succeeded in creating a sustainable asset development system and providing a multiplier effect for improving the welfare of heirs and the surrounding community. The business model developed shows innovation in three aspects: Integration of digital technology in the operational management of inheritance assets, development of a tiered profit-sharing system between heirs and managers, and implementation of a Sharia-based sustainability program. The socioeconomic impact is identified through the creation of more than 200 jobs, the strengthening of the local economy, and the development of community capacity.